2020
DOI: 10.3390/math8081314
|View full text |Cite
|
Sign up to set email alerts
|

Schedule Execution for Two-Machine Job-Shop to Minimize Makespan with Uncertain Processing Times

Abstract: This study addresses a two-machine job-shop scheduling problem with fixed lower and upper bounds on the job processing times. An exact value of the job duration remains unknown until completing the job. The objective is to minimize a schedule length (makespan). It is investigated how to best execute a schedule, if the job processing time may be equal to any real number from the given (closed) interval. Scheduling decisions consist of the off-line phase and the on-line phase of scheduling. Using the fixed lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Based on our literature research, no papers have been found considering a job-shop with sequence-dependent setup times and preventive maintenance, where the processing times are unknown at the beginning. Previously mentioned Sotskov et al (2020) shows the most comparable research with having uncertain products times until the product is produced, without sequence-dependent setup times and preventive maintenance. Naderi et al (2009) investigates sequence-dependent setup times and preventive maintenance in job-shop scheduling, however they considered all processing times to be known at the start.…”
Section: Naderimentioning
confidence: 98%
See 1 more Smart Citation
“…Based on our literature research, no papers have been found considering a job-shop with sequence-dependent setup times and preventive maintenance, where the processing times are unknown at the beginning. Previously mentioned Sotskov et al (2020) shows the most comparable research with having uncertain products times until the product is produced, without sequence-dependent setup times and preventive maintenance. Naderi et al (2009) investigates sequence-dependent setup times and preventive maintenance in job-shop scheduling, however they considered all processing times to be known at the start.…”
Section: Naderimentioning
confidence: 98%
“…This still considers much information known in advance of the production process, which is unrealistic due to many factors that can influence the actual processing times. Sotskov et al (2020) researched a two-machine job-shop with uncertain processing times but did not consider maintenance or sequence-dependent setup times. Lou et al (2012) researched reactive scheduling, using an initial schedule, based on unexpected events in the simulation environment.…”
Section: Naderimentioning
confidence: 99%
“…The flexible JSSP extends the deterministic JSSP by allowing a machine operation to be processed by one machine out of a set of machines, thereby adding the problem of assigning each operation to a specific machine (routing) [41]. Stochastic JSSPs introduce parameters dealing with probability conditions, for instance, machine breakdown or processing time [16]. Since real-world JSSP times often don't have deterministic value, fuzzy values (processing times, due date, ranking) have been incorporated into JSSP, hence the name fuzzy JSSP [43].…”
Section: Related Work Jssp Classes and Typesmentioning
confidence: 99%
“…Sotskov et al [17] consider the two-machine job-shop scheduling problem with interval processing times and makespan minimization. The focus of this paper is how to execute a schedule in the best way.…”
mentioning
confidence: 99%